Expression of heterologous oxalate decarboxylase in HEK293 cells confers protection against oxalate induced oxidative stress as a therapeutic approach for calcium oxalate stone disease - Abhishek Albert (Journal of Enzyme Inhibition and Medicinal Chemistry, 2017)
Oxalates stimulate alterations in renal epithelial cells and thereby induce calcium oxalate (CaOx) stone formation. Bacillus subtilis YvrK gene encodes for oxalate decarboxylase (OxdC) which degrades oxalate to formate and CO2. The present work is aimed to clone the oxdC gene in a mammalian expression vector pcDNA and transfect into Human Embryonic Kidney 293 (HEK293) cells and evaluate the oxdC expression, cell survival rate and oxalate degrading efficiency. The results indicate cell survival rate of HEK293/pcDNAOXDC cells pre-incubated with oxalate was enhanced by 28%. HEK293/pcDNAOXDC cells expressing OxdC treated with oxalate, significantly restored antioxidant activity, mitochondrial membrane potential and intracellular reactive oxygen species (ROS) generation compared with HEK293/pcDNA. Apoptotic marker caspase 3 downregulation illustrates HEK293/pcDNAOXDC cells were able to survive under oxalate-mediated oxidative stress. The findings suggest HEK293 cells expressing oxdC capable of degrading oxalate protect cells from oxidative damage and thus serve as a therapeutic option for prevention of CaOx stone disease.